IMPROVEMENT OF CULTURAL PASTURES IN KARAKALPAKSTAN - Bekmurat Kh. Turdyshev,; Nietbay B. Reimov, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
In the Republic of Karakalpakstan, located on the southern coast of the Aral Sea, it is necessary to expand and strengthen the area of ​​​​cultivated pastures to increase the productivity of livestock, create a green landscape and the environment due to a decrease in pasture productivity due to global climate change, water scarcity and increasing salinity of the soil cover.